“I Need This Person’s Support to Have a Career”: The Material and Emotional Impacts of Neoliberalism on Trans Collegians’ Classroom Experiences at a Public University - Gutzwa, Justin A.; Marx, Robert A. (Critical Education, 2025)
Neoliberal capitalism has undoubtedly impacted every sphere of public education in the United States. With an increased push towards identity-neutral modalities of instruction, students who identify as transgender, non-binary, or other expansive gender identities (trans) are forced to reckon with implicit and explicit power dynamics in classrooms that prioritize white, cisheteropatriarchal modes of knowledge production in nuanced ways. This qualitative study explores the ways neoliberal capitalism impacts the curricular experiences of trans students by centering the power dynamics they encounter through interactions with their professors and their peers. Findings underscore the pernicious nature of the neoliberalization of higher education in advancing trans exclusion from collegiate classrooms as a hindrance towards equity in public postsecondary education. Implications for transforming curricular instruction and policy to subvert the tensions of neoliberalism are also provided.